2018
DOI: 10.1021/acs.joc.8b00553
|View full text |Cite
|
Sign up to set email alerts
|

Stendomycin and Pantomycin Are Identical Natural Products: Preparation of a Functionalized Bioactive Analogue

Abstract: The natural products pantomycin and stendomycin were both reported as antimicrobial agents. We demonstrate by gene cluster analysis, LC-MS analysis, and isolation that these polypeptides are identical, and we identify previously unknown congeners. We show that stendomycin can be chemically modified at its electrophilic dehydrobutyrine moiety yielding the first bioactive analogue of this natural product which can undergo additional functionalization. This compound may be a valuable starting point for molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…This BGC (region 32.1, candidate BGC 35 kb; Supplementary Table S6 ) contains a N-terminal acyl ligase domain, which is associated with lipopeptide biosynthesis ( Kersten et al, 2011 ), in addition to NRPS modules. It further shares sequence similarity with Streptomyces RTd22 ( Chagas et al, 2016 ) and ATCC53653 BGCs, the latter reported previously as a producer of stendomycin lipopeptides— Supplementary Figures S11 , S12 ; Supplementary Table S5 ( Kersten et al, 2011 ; Villadsen et al, 2018 ). A complex regulatory system is found within this BGC, which harbours TetR, LysR, sensor histidine kinase, SARP, and LuxR regulators.…”
Section: Resultssupporting
confidence: 61%
“…This BGC (region 32.1, candidate BGC 35 kb; Supplementary Table S6 ) contains a N-terminal acyl ligase domain, which is associated with lipopeptide biosynthesis ( Kersten et al, 2011 ), in addition to NRPS modules. It further shares sequence similarity with Streptomyces RTd22 ( Chagas et al, 2016 ) and ATCC53653 BGCs, the latter reported previously as a producer of stendomycin lipopeptides— Supplementary Figures S11 , S12 ; Supplementary Table S5 ( Kersten et al, 2011 ; Villadsen et al, 2018 ). A complex regulatory system is found within this BGC, which harbours TetR, LysR, sensor histidine kinase, SARP, and LuxR regulators.…”
Section: Resultssupporting
confidence: 61%
“…In fact, enzyme-catalyzed conjugate additions of thiols to ΔAla and ΔAbu are involved in the biosynthesis of lantibiotics . However, a close look at the literature reveals that uncatalyzed conjugate additions of thiols to ΔAAs larger than ΔAla typically require large excesses of thiol to proceed . Alternatively, placement of the ΔAA at the C -terminus of a peptide instead of embedded within the backbone can increase its electrophilicity .…”
Section: Resultsmentioning
confidence: 99%
“…121 Recent structural elucidation has revealed that pantomycin is in fact identical to stendomycin. 122 2.1.11 Enduracidins. Enduracidin A and B are produced by S. fungicidicus no.…”
Section: Reviewmentioning
confidence: 99%
“…121 Recent structural elucidation has revealed that pantomycin is in fact identical to stendomycin. 122…”
Section: Identification and Biosynthesis Of Lipopeptides From Strepto...mentioning
confidence: 99%